Synthesis and biological evaluation of glycophorphyrins for use as photodynamic therapy agents - Daly, Robin (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
Photodynamic therapy (PDT) is a light activated anti-cancer treatment. Reagents for PDT have advanced dramatically since the earliest porphyrin based oligomers. Ultimately the focus is on improving the efficacy of these agents, and the quality of life for the patients. With the current 3rd generation of PDT agents, emphasis is now focused on the improved targeting of these drugs to the required site. The ability of carbohydrates to act both as targeting and solubilising agents, has led to the synthesis and biological testing of a library of glycoporphyrin PDT agents.
Keywords: Chemistry Ph.D.; Ph.D. Trinity College Dublin.